Primary surgical management of anterior pelvic organ prolapse: a systematic review, network meta‐analysis and cost‐effectiveness analysis. (18th October 2019) - Slade, E; Daly, C; Mavranezouli, I; Dias, S; Kearney, R; Hasler, E; Carter, P; Mahoney, C; Macbeth, F; Delgado Nunes, V
Abstract : Background: Anterior compartment prolapse is the most common pelvic organ prolapse (POP) with a range of surgical treatment options available. Objectives: To compare the clinical effectiveness and cost‐effectiveness of surgical treatments for the repair of anterior POP. Methods: We conducted a systematic review of randomised controlled trials comparing surgical treatments for women with POP. Network meta‐analysis was possible for anterior POP, same‐site recurrence outcome. A Markov model was used to compare the cost–utility of surgical treatments for the primary repair of anterior POP from a UK National Health Service perspective. Main results: We identified 27 eligible trials for the network meta‐analysis involving eight surgical treatments tested on 3194 women. Synthetic mesh was the most effective in preventing recurrence at the same site. There was no evidence to suggest a difference between synthetic non‐absorbable mesh, synthetic partially absorbable mesh, and biological mesh. The cost–utility analysis, which incorporated effectiveness, complications and cost data, found non‐mesh repair to have the highest probability of being cost‐effective. The conclusions were robust to model inputs including effectiveness, costs and utility values. Conclusions: Anterior colporrhaphy augmented with mesh appeared to be cost‐ineffective in women requiring primary repair of anterior POP. There is a need for further research on long‐term effectiveness and the safety of mesh products to establish their relative cost‐effectiveness with a greater certainty. Tweetable abstract: New study finds mesh cost‐ineffective in women with anterior pelvic organ prolapse. Tweetable abstract: New study finds mesh cost‐ineffective in women with anterior pelvic organ prolapse.